A Real-Business-Cycle model with institutional quality: The Case of Bulgaria (1999-2018) - Aleksandar Vasilev (Review of Economics, 2021)
This paper takes an otherwise standard real-business-cycle (RBC) setup with government sector, and augments it with an output-expropriation mechanism and shocks to institutional quality in order to study business cycle fluctuations. The extraction decision is endogenous: households can use their time either productively, or engage in opportunistic activities. Stronger institutions decrease the size of the available resources for capture, and suppress corrupt behavior. As a test case, the model is calibrated to Bulgaria after the introduction of the currency board (1999-2018). Overall, the shocks to institutional quality generate business cycles of the same magnitude as in data, which suggests that political economy factors might be the major driving force behind the observed economic fluctuations in Bulgaria. Another interesting result, generated by the model, is that on average, the estimated size of evaded resources is approximately one-fourth of output, which is very close to the estimates of the unofficial economy share, e.g., European Commission (2014) and Medina and Schneider (2017).
Keywords: E32; E26; E62; 330; institutional quality; output evasion; business cycles; Bulgaria